Angiotensin II receptor binding sites in brain microvessels. - Speth, R C (1985)
We assessed the specific binding of 125I-labeled angiotensin II (125I-Ang II) to particulate fractions of the cerebral cortex and cerebellum and to microvessels obtained by bulk isolation from these two brain regions in the dog. 125I-Ang II binds to cerebral and cerebellar microvessels in a specific, saturable, and reversible manner and with high affinity (dissociation constant about 1 nM). Maximal binding of 125I-Ang II to brain microvessels was about 2-fold higher than the maximal binding to particulate fractions of the cerebellum and more than 15-fold higher than that of the cerebral cortex. No significant differences were noted between cerebral and cerebellar microvessels in their specific binding of Ang II. Furthermore, our finding that analogues of Ang II displace specific 125I-Ang II binding to brain microvessels in a rank order that correlates with their pharmacological activities confers biological relevance on the ligand-binding studies. These results strongly suggest that specific Ang II receptor binding sites are present in brain microvessels. Such Ang II receptors may have an important role in regulating the microcirculation of the brain.